The crucial role of fluorine in fully alkylated ladder type carbazole based non-fullerene organic solar cells - He,Q; Shahid,M; Jiao,X; Gann,E; Eisner,F; Wu,T; Fei,Z; Anthopoulos,TD; McNeill,CR; Heeney,MJ (ACS Applied Materials and Interfaces, 2020)
Two fused ladder type non-fullerene acceptors, DTCCIC and DTCCIC-4F, based on an electron-donating alkylated dithienocyclopentacarbazole core flanked by electron-withdrawing non-fluorinated or fluorinated 1,1-dicyanomethylene-3-indanone (IC or IC-4F), are prepared and utilized in organic solar cells (OSCs). The two new molecules reveal planar structures and strong aggregation behavior, and fluorination is shown to red shift the optical band gap and down shift energy levels. OSCs based on DTCCIC-4F exhibit a power conversion efficiency of 12.6 %, much higher than that of DTCCIC based devices (6.2 %). Microstructural studies reveal that while both acceptors are highly crystalline, bulk heterojunction blends based on the non-fluorinated DTCCIC result in overly coarse domains, while blends based on the fluorinated DTCCIC-4F exhibit a more optimal nanoscale morphology. These results highlight the importance of end group fluorination in controlling molecular aggregation and miscibility.